2014
DOI: 10.3109/14767058.2013.878695
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of prenatal risk factors for prediction of outcome in right heart lesions: CVP Score in fetal right heart defects

Abstract: The original Cardiovascular Profile Score predicted the risk of death in right heart defects. The modified score was not validated as a good prediction tool by this study. Fetal RV pressure estimate and peak aortic velocity can be used as independent prognostic predictors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…It is not always easy to accurately evaluate the severity of tricuspid valve regurgitation. 4 The gap in timing between atrial contraction and atrioventricular valve closure because of fetal arrhythmia can affect venous Doppler sonography findings. In the future, a further large study should be performed to clarify whether AF NT-proBNP levels can complement echocardiographic assessment in fetuses with CHD or arrhythmia.…”
Section: Study Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not always easy to accurately evaluate the severity of tricuspid valve regurgitation. 4 The gap in timing between atrial contraction and atrioventricular valve closure because of fetal arrhythmia can affect venous Doppler sonography findings. In the future, a further large study should be performed to clarify whether AF NT-proBNP levels can complement echocardiographic assessment in fetuses with CHD or arrhythmia.…”
Section: Study Strengths and Limitationsmentioning
confidence: 99%
“…2 The CVP score has been studied in relation to prognosis in fetuses with congenital heart defects (CHD). [3][4][5][6] In pediatric and adult cardiology, atrial natriuretic peptide (ANP), B-type natriuretic peptide (BNP), and N-terminal pro-brain natriuretic peptide (NT-proBNP) are established markers of HF. 7-9 Our previous study investigating the correlation between plasma NP levels and HF assessed by CVP score in fetuses with CHD or arrhythmia demonstrated that plasma NP levels reflect the severity of fetal HF.…”
mentioning
confidence: 99%
“…Our previous report demonstrated that the CVP score is a useful echocardiographic marker for predicting acute intrapartum non‐reassuring fetal status in infants with CHD . However, few studies have investigated CVP score as it relates to prognosis in infants with CHD . Wieczorek et al retrospectively investigated 131 singleton pregnancies with a diagnosis of fetal CHD, and they concluded that CVP score ≤ 7 was a risk factor for perinatal death .…”
Section: Discussionmentioning
confidence: 99%
“…High CVP and BP scores in utero cannot reflect low mortality after birth in cases with these conditions. Conversely, infants with Ebstein's anomaly or tricuspid valve dysplasia with a circular shunt have low CVP and BP scores, lead to high perinatal mortality . Whereas abnormal venous Doppler findings are more common in infants with right heart obstructive lesions such as pulmonary atresia with intact ventricular septum; however, these changes do not necessarily indicate fetal heart failure .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation